Manufacturing Home. Issue 2 (20th November 2019) - Shapiro, Nicholas
Abstract: Making the colonist's home mobile, disregarding local ecologies and building practices, is foundational to the settler‐colonial project. This article tracks the mobile home from its role as a key architecture of occupation and settlement by the British Empire to being a superlative embodiment of hydrocarbon‐infused commodities and homes after World War II. As the violences of mobile home ownership are coterminous with the violences of settler colonialism, an equitable vision of affordable housing cannot stop at achieving racial parity for toxic/classist loans (for often toxic homes) or greater protections for colonial land tenure.